Price decomposition of laser treatment for port-wine stain using the hedonic pricing model - Jantarakolica T. (2023)
Background: Port-wine stain (PWS) is a congenital capillary malformation associated with negative effects on the quality of life and psychological health of the patients. Pulsed dye laser (PDL) is the current treatment of choice for PWS; however, there is little information on the factors determining the treatment price of PWS. We aim to explore the factors determining the treatment price of PWS. Methods: Data were collected through telephone surveys and self-reported questionnaires from hospitals, chain clinics, and doctor's offices that offered PWS treatment from February 1 to March 30, 2021. Data were analyzed by descriptive statistics and multivariate analysis using a log-linear regression model. Results: A total of 104 observations were gathered. The estimated base price of the treatment without any additional features is 98.34 USD. Treatment by dermatologists has an additional charge of 28.41 USD or 28.9%. Some private clinics offer a lower price of 28.7% (or 28.27 USD) by illegally having non-medical doctors perform the treatment. Treatment with 595-nm PDL and 585-nm PDL and 1064-nm Nd:YAG lasers has an additional charge of 34% (or 33.45 USD) and 38% (or 37.41 USD), respectively. The location and type of medical facility can also affect the price of the treatment. Conclusion: Many factors determine the base price and shadow price of PWS treatment. Factors determining a higher cost of laser fee includes non-government facilities, location within the capital city, and shopping complexes (high-cost location). Lastly, the type of laser and medical personnel provider can also affect the price of the treatment.